2016
DOI: 10.1073/pnas.1601954113
|View full text |Cite|
|
Sign up to set email alerts
|

Leveraging abscisic acid receptors for efficient water use in Arabidopsis

Abstract: Plant growth requires the influx of atmospheric CO 2 through stomatal pores, and this carbon uptake for photosynthesis is inherently associated with a large efflux of water vapor. Under water deficit, plants reduce transpiration and are able to improve carbon for water exchange leading to higher water use efficiency (WUE). Whether increased WUE can be achieved without trade-offs in plant growth is debated. The signals mediating the WUE response under water deficit are not fully elucidated but involve the phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
141
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(160 citation statements)
references
References 47 publications
(66 reference statements)
1
141
1
1
Order By: Relevance
“…It is possible that a smaller stomata aperture affects the water use efficiency (WUE) of the resistant Aly and Esa . Importantly, a recent overexpression screen found that higher levels of the Aly ‐ and Esa ‐elevated ABA receptors increase Ath WUE (Yang et al ., ; Tischer et al ., ), suggesting a causal contribution to Aly and Esa drought resistance. While the functional orthology of the Aly and Esa proteins remains to be shown, this possibly convergent evolution of higher ABA receptor levels in Aly and Esa is consistent with their resistant phenotype.…”
Section: Resultsmentioning
confidence: 96%
“…It is possible that a smaller stomata aperture affects the water use efficiency (WUE) of the resistant Aly and Esa . Importantly, a recent overexpression screen found that higher levels of the Aly ‐ and Esa ‐elevated ABA receptors increase Ath WUE (Yang et al ., ; Tischer et al ., ), suggesting a causal contribution to Aly and Esa drought resistance. While the functional orthology of the Aly and Esa proteins remains to be shown, this possibly convergent evolution of higher ABA receptor levels in Aly and Esa is consistent with their resistant phenotype.…”
Section: Resultsmentioning
confidence: 96%
“…Overexpression of the rate-limiting enzyme in ABA biosynthesis, 9-cis-epoxycarotenoid dioxygenase (NCED), led to increased ABA accumulation (Thompson et al, 2000), lower stomatal conductance, and up to 79% higher gravimetric transpiration efficiency (another term for WUE) with only small effects on photosynthetic carbon assimilation or growth (Thompson, Andrews, et al, 2007). Similarly, in Arabidopsis and wheat, activation of ABA signalling through manipulation of ABA receptors led to an increase in WUE of up to 40% without impacting growth significantly (Mega et al, 2019;Papacek, Christmann, & Grill, 2019;Yang et al, 2016). The use of candidate genes therefore holds huge promise for the production of crops with enhanced WUE.…”
mentioning
confidence: 99%
“…The moderate effects of subfamily II members on the ABA response at basal ABA levels make these RCARs prime candidates to reduce transpiration under nonstress conditions without curbing photosynthesis. Recent analysis of all Arabidopsis RCARs showed that overexpression of two subfamily II members, RCAR6/PYL12 and RCAR10/PYL4, increased water-use efficiency and resulted in water-productive plants, which are characterized by reduced transpiration with little or no trade-offs in CO 2 uptake and biomass accumulation (49). Important for the trait is the altered ABA response at resting ABA levels.…”
mentioning
confidence: 99%